2021
DOI: 10.1111/inm.12816
|View full text |Cite
|
Sign up to set email alerts
|

Exploring pedagogies used in undergraduate mental health nursing curriculum: An Integrative Literature Review

Abstract: The growing demand of mental health services among the population and the stigma associated with mental health conditions have resulted in a shortage of skilled nurses competent in delivering quality care to persons experiencing mental health conditions. This suggests the need to develop a systematic and comprehensive curriculum to prepare nursing students for a career in mental health nursing. An integrative review on empirical studies was conducted based on Cooper's five-stage integrative review framework to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Firstly, the use of virtual simulations may be further explored such that learning of clinical skills may take place in the comfort of the students’ homes. The field of virtual reality and simulations have been advancing in recent years [ 38 ] and have been used in nursing curriculums [ 39 ]. With the rapid expansion of virtual technology, it would be wise for teaching institutions to leverage these to provide distanced learning opportunities for students.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the use of virtual simulations may be further explored such that learning of clinical skills may take place in the comfort of the students’ homes. The field of virtual reality and simulations have been advancing in recent years [ 38 ] and have been used in nursing curriculums [ 39 ]. With the rapid expansion of virtual technology, it would be wise for teaching institutions to leverage these to provide distanced learning opportunities for students.…”
Section: Discussionmentioning
confidence: 99%
“…Important curriculum preparation, per the respondents, is an adequate aspect in motivating learners according to Porter et al (2020). Goh et al (2021) has often said that lack of curriculum development is one of the causes that contribute to pupils' lack of enthusiasm. Furthermore, the intense load of coursework was one cause for nursing students dropping out during the early stages of the program.…”
Section: Discussionmentioning
confidence: 99%
“…This is an encouraging finding, since it demonstrates a willingness among the undergraduates to move past traditional biomedical approaches and to embrace cooperation for a more meaningful recovery process for the PMHCs. In this context, evidence has suggested that the involvement of PMHCs in the pedagogical process can provide much-needed nuances in these discussions [ 23 ]. In addition, such an opportunity can provide preliminary experiences for the undergraduates to directly converse with PMHCs and understand their journey towards recovery, better aligning with how curriculums in countries where personal recovery is more emphasized are evolving.…”
Section: Discussionmentioning
confidence: 99%
“…While the incorporation of consumer involvement in the nursing curriculum has been highlighted in the literature [ 23 ], investigations into medical students’ knowledge of and attitudes towards personal recovery have been scarce, especially in an Asian country. Hence, this study aimed to explore medical undergraduates’ perceptions of recovery for PMHCs through the following research questions: (1) What are the medical undergraduates’ views on mental illnesses and mental well-being?…”
Section: Introductionmentioning
confidence: 99%